Sweetened areca-nut chewing habit: A public health issue among school children of Indore, India (South East Asia Journal of Public Health, 2013)
Chewing of the areca-nut usually starts early in life leading to a multitude of problems in adulthood. The areca-nut can be correlated with an increased incidence of cancer. Like tobacco, chewing the areca-nut also leads to oral and oro-pharyngeal cancers. The areca-nut is usually marketed in the form of a sweetened areca-nut (locally known as sweet supari) to target young children. A high proportion of school children use areca-nut daily in some form. This study was conducted to determine the prevalence of sweetened areca-nut use and assess the awareness of health risks among school students of Indore, India. Till date none of the studies have pointed out the prevalence of sweet-ened areca use. Population based studies on the habit of areca-nut chewing among children from the district of Indore, Central India have not been reported earlier in the studies. In our study we found 81% of the children used the sweetened form of the areca-nut. Fifty five percent of areca-nut users reported that they learnt the habit from their friends or siblings. The majority of the users (70.4%) were unaware of the harmful effects of areca-nut use, and only a few were aware that it may cause cancer or oral submucous fibrosis. Government school children are more involved in areca-nut chewing habit. Boys were more indulged than girls. Actively communicating the areca-nuts health risks to the public, and creating strategies involving parents, teachers and local communities could be initiated to discourage areca-nut use. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15959 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 73-76